ANALISIS PENGARUH PENGGUNAAN SISTEM INFORMASI BERBASIS KOMPUTER TERHADAP KUALITAS KERJA DAN KEPUASAN KERJA PEGAWAI ( STUDI PADA BIRO PENGELOLAAN KEUANGAN SEKDA PROVINSI BENGKULU) - Abdullah, Abdullah; Kurniawan, Ade (UNIB Press, 2014)
The purpose of this study is to see the effect of the use of Computer-Based Information System for Employees’ Job Satisfaction and Quality of Work. Independent variables used in this study is Computer Based Information Systems. For the dependent variables used in this study is Employees’ Job Satisfaction and Quality of Work. The data in this study are primary data obtained from questionnaires spread directly to the employees who work at the Bureau of Finance Management of Bengkulu Province Secretariat. Questionnaire data that can be processed were from 48 respondents that considered to represent the population of employees who work at the Bureau of Finance Management. The test of data in this study used multiple linear regression analysis with SPSS 16. The results in this study indicate two different conclusions, the first stating that the use of computer-based information system did not affect the Quality of Work of employees, while the latter results suggest that the use of computer-based information systems had a positive and significant effect on Job Satisfaction of employees in the Bureau of Finance Management of Bengkulu Province Secretariat.